Olaratumab combined with doxorubicin and ifosfamide overcomes individual doxorubicin and olaratumab resistance of an undifferentiated soft-tissue sarcoma in a PDOX mouse model. (1st June 2019) - Higuchi, Takashi; Miyake, Kentaro; Sugisawa, Norihiko; Oshiro, Hiromichi; Zhang, Zhiying; Razmjooei, Sahar; Yamamoto, Norio; Hayashi, Katsuhiro; Kimura, Hiroaki; Miwa, Shinji; Igarashi, Kentaro; Bouvet, Michael; et al.
Abstract: Olaratumab (OLA), a monoclonal antibody against platelet-derived growth factor receptor alpha (PDGFRα), has recently been used against soft-tissue sarcoma (STS) combined with doxorubicin (DOX), with limited efficacy. The goal of the present study was to determine the efficacy of OLA in combination with DOX and ifosfamide (IFO) on STS. Undifferentiated soft-tissue sarcoma (USTS) from a striated muscle of a patient was grown orthotopically in the right biceps femoris muscle of nude mice to establish USTS patient-derived orthotopic xenograft (PDOX) model. USTS PDOX tumors were treated with OLA alone, DOX alone, DOX combined with IFO, OLA combined with DOX or IFO, and OLA combined with DOX and IFO. Tumor size and body weight were measured during the 14 days of treatment. Tumor growth was arrested by OLA combined with DOX and IFO. Tumors treated with OLA combined with DOX and IFO had the most necrosis. The present study demonstrates the power of the PDOX model to identify the novel effective treatment strategy of the combination of OLA, DOX and IFO for soft-tissue sarcomas. Highlights: Undifferentiated soft-tissue sarcoma (USTS) are recalcitrant neoplasms. Determined the efficacy of Olaratumab (OLA) plus doxorubicin (DOX) and ifosfamide (IFO) on USTS. First study which shows that OLA plus DOX and IFO combination is active in USTS. Combination of OLA plus DOX and IFO could be a promising novel therapy for USTS.